Comparative Prey Spectra Analyses on the Endangered Aquatic Carnivorous Waterwheel Plant (Aldrovanda vesiculosa, Droseraceae) at Several Naturalized Microsites in the Czech Republic and Germany - Horstmann, M; Heier, L; Kruppert, S; Weiss, L C; Tollrian, R; Adamec, L; Westermeier, A; Speck, T; Poppinga, S (Integrative organismal biology (Oxford, England), 2019)
The critically endangered carnivorous waterwheel plant (Aldrovanda vesiculosa, Droseraceae) possesses underwater snap traps for capturing small aquatic animals, but knowledge on the exact prey species is limited. Such information would be essential for continuing ecological research, drawing conclusions regarding trapping efficiency and trap evolution, and eventually, for conservation. Therefore, we performed comparative trap size measurements and snapshot prey analyses at seven Czech and one German naturalized microsites on plants originating from at least two different populations. One Czech site was sampled twice during 2017. We recorded seven main prey taxonomic groups, that is, Cladocera, Copepoda, Ostracoda, Ephemeroptera, Nematocera, Hydrachnidia, and Pulmonata. In total, we recorded 43 different prey taxa in 445 prey-filled traps, containing in sum 461 prey items. With one exception, prey spectra did not correlate with site conditions (e.g. water depth) or trap size. Our data indicate that A. vesiculosa shows no prey specificity but catches opportunistically, independent of prey species, prey mobility mode (swimming or substrate-bound), and speed of movement. Even in cases where the prey size exceeded trap size, successful capture was accomplished by clamping the animal between the traps' lobes. As we found a wide prey range that was attracted, it appears unlikely that the capture is enhanced by specialized chemical- or mimicry-based attraction mechanisms. However, for animals seeking shelter, a place to rest, or a substrate to graze on, A. vesiculosa may indirectly attract prey organisms in the vicinity, whereas other prey capture events (like that of comparably large notonectids) may also be purely coincidental.